Climatic and hydrologic processes leading to recent wetland losses in Yellowstone National Park, USA - Schook, Derek M., author; Cooper, David J., advisor; Ronayne, Michael J., committee member; Kampf, Stephanie K., committee member (Colorado State University. Libraries, 2012)
Wetlands provide vital habitat within functioning environments and act as landscape indicators by integrating catchment-scale hydrologic processes. Wetland drying during the past few decades in Yellowstone National Park's Northern Range has caused concern among National Park managers and the public at large. My research was initiated to develop an understanding of the processes controlling wetland water levels and contributing to wetland decline in the Northern Range. To do this I integrated analyses of hydrology, climate, soils, and vegetation. In 2009 I selected 24 study wetlands and instrumented each with an average of five shallow groundwater monitoring well-and-piezometer nests. To quantify historic wetland area I mapped hydric soils, analyzed aerial photographs, and identified geomorphic indicators of higher water. Vegetation was sampled to characterize wetlands and plant-water relationships, and I also conducted a soil seed bank study. The Trumpeter Lake focal site revealed groundwater changes through time and was used to identify the timescale on which an important wetland varies. Climate data indicated that warming and drying occurred during the 20th century, but that this pattern was within the natural range of variation for the study region during the past 800 years. Hydrologic data revealed that study sites included locations of groundwater discharge, recharge, and flow-through as well as water perched above the regional water table. Hydrologic regimes were classified using a shape-magnitude framework and seven wetland classes were characterized. Wetland classes exhibited variable hydrologic permanence within and between the two study summers. Aerial photographs and hydric soil delineation both confirmed formerly greater wetland abundance. These changes were linked to the wetland classes and the presence or absence of surface water outlets. Wetland plant species inhabited areas of distinct water table depth and variation, and can be used to infer subsurface hydrologic regime in the absence of extensive monitoring well networks. Continued monitoring of these wetland basins and their watersheds is critical to expanding our understanding of the processes supporting Northern Range wetlands and allowing us to better manage these valuable habitats.
Keywords: climate change; wetland; hydrology; Yellowstone National Park